Psychological dynamics of executive functions in university students with high anxiety trait - Teleb, Ahmed A.; Diab, Asmaa O.; Abbady, Adel S.; Abdelmagid, Ahmed S.; Ibrahim, Asem M. (International Journal of Innovative Research and Scientific Studies, 2025)
This research aimed to investigate the correlation between anxiety and executive functions (EF) among university students with trait anxiety and to clarify the psychological dynamics of their EF. Two hundred forty-three undergraduate students (Mage = 19.97 years; SD = .75) completed the State-Trait Anxiety Inventory (STAI-t) and the Behavior Rating Inventory of Executive Function, while five of them with high anxiety traits were selected to complete the Rorschach Inkblot test. The results showed that there was a statistically significant correlation between anxiety and deficiencies in the functions of initiation and shifting, working memory, inhibition, and emotional regulation, while there was no significant correlation for the other functions. The application of the Rorschach test showed that cases were characterized by complex cognitive activity that is used more defensively than in a healthy exploratory way; the cases are capable of attention, planning, and excessive control because of their dependence on the cognitive accuracy of the cards. The deficiency lies in the function of emotional regulation, which inevitably affects their development and characterizes it as heterogeneous, necessitating weakness in multiple psychological areas, without requiring deterioration or disintegration.